Rapidly Destructive Inflammatory Arthritis of the Hip - Jenny Shu; Ian Ross; Bret Wehrli; Richard W. McCalden; Lillian Barra (Case Reports in Rheumatology)
Rapidly destructive coxarthrosis (RDC) is a rare syndrome that involves aggressive hip joint destruction within 6–12 months of symptom onset with no single diagnostic laboratory, pathological, or radiographic finding. We report an original case of RDC as an initial presentation of seronegative rheumatoid arthritis (RA) in a 57-year-old Caucasian woman presenting with 6 months of progressive right groin pain and no preceding trauma or chronic steroid use. Over 5 months, she was unable to ambulate and plain films showed complete resorption of the right femoral head and erosion of the acetabulum. There were inflammatory features seen on computed tomography (CT) and magnetic resonance imaging (MRI). She required a right total hip arthroplasty, but arthritis in other joints showed improvement with triple disease modifying antirheumatic drugs (DMARD) therapy and almost complete remission with the addition of adalimumab. We contrast our case of RDC as an initial presentation of RA to 8 RDC case reports of patients with established RA. Furthermore, this case highlights the importance of obtaining serial imaging to evaluate a patient with persistent hip symptoms and rapid functional deterioration.